Experiências insustentáveis e pequenos gestos de sustentação em uma casa-serviço - Polastrini, Julliana Borges [UNIFESP] (2019)
Normality as a requirement appears as an important feature in contemporary subjectivation policies with implications in an Therapeutic Residential Service (TRS) work. With the statements of equality, rights and a society clear of insane asylums, the strategy to take away their institutional character disintegrates the cloister and can allow the arise of an individual with rights, liberal, socially included, in leisure, at work, in consumption, etc. To transform a health service (therapeutic) into a home, is one of the statements turned into problems in this investigation with an house-TRS in Cidade Ademar, in the city of São Paulo. In everyday life we find a certain hybridity in the ―house-TRS‖ with multiple stresses in life management modes. Crossed by the discourse of deinstitutionalization and psychiatric reform, this research tried to give readability to what seemed to be integral and institutionalized in this proposal of ongoing deinstitutionalization. Brands, minimal gestures and experiences have come up with people living in a house-TRS involving house, city, health workers and subjectivation policies. The production of narratives was one of the strategies to give thickness to this investigation, they carry marks of the arrival into the house, the appropriation of the space and the adjustment of relationships. These narratives were not performed to praise, oppose or militate, but rather to allow vital questions and the possibility of finding different relationships with the madness, the house, with the unsustainable that crosses us daily. The accompaniment of the lives inside the house, working there, researching, was done in blocks, in pieces: a love, a yard, a joy, a room, a health, a living room, a death, a policy, a closet, etc. With these problems and very concrete pieces, we started thinking about the deinstitutionalization as an institution. With this line of thought, the research attempted to construct credible images, tried to create new perceptions, follow a deinstitutionalization project in us, with what we want and we talk every day. By narrative images, I tried to express experiences of a house- TRS with its topological disputes, zones of political asylum liberator, bughouse, normopathy, in certain cases scrutinizing an TRS political asylum that shelters, protects and also can be a "school of administrative alienation". These are small blocks, that were written with the lives of residents who left the bughouse, now inhabited by other tensions in the house-TRS. A difficult support, with diverse effects, focusing on politics, lovingness, work of groping what vibrates and happens in the everyday life of a house-TRS, with vital experiences, undocked, liberations of what they say is humanization, a certain civilizing adhesion, adjusting modes of existence. An ethical- clinical-political research of blocks research, pieces of a production, surveys of untamed lives, with docilizations, discipline, control, etc. Accompanying the occupation of a room, a yard and no longer a bughouse courtyard, with good and bad encounters, disinvesting dressage and submission even with the insistence of walls that rise in the relations with health and madness.